O libro da filla or the Promise of (Un)Happiness according to Inma López Silva - Moszczyńska-Dürst, Katarzyna (Madrygal. Revista de Estudios Gallegos, 2021)
The aim of this article is to analyse the representation of performative (un) happiness, with its mandates, promises, taboos and failures as codified in O Libro da Filla (2020), the last novel of the Galician writer Inma López Silva. Parting from the critical theory of emotions elaborated by Sara Ahmed in The promise of happiness (2010), I will see how the protagonists in the analysed text associate happiness with certain social roles, places, rituals or lifestyles, or even with certain ways of comprehending and experiencing the world. The above “happy objects” are imposed on them by the dominant cultural logic as guarantors of the “good life” and “scripts” of normative conduct. Likewise, we I will verify how and to what social extent the promotion of happy regulations conceals the “the psychic life of power” and causes the emergence of melancholy. Finally, the analysis of O Libro da Filla should reveal the political potential that lies in the archives of unhappiness and in the act of writing.